Public job-creation programs: The economic benefits of investing in social care? Case studies in South Africa and the United States - Rania Antonopoulos; Kijong Kim (Levy Economics Institute of Bard College, 2011)
This paper demonstrates the strong impacts that public job creation in social care provisioning has on employment creation. Furthermore, it shows that mobilizing underutilized domestic labor resources and targeting them to bridge gaps in community-based services yield strong pro-poor income growth patterns that extend throughout the economy. Social care provision also contributes to promoting gender equality, as women - especially from low-income households - constitute a major workforce in the care sector. We present the ex-ante policy simulation results from two country case studies: South Africa and the United States. Both social accounting matrix-based multiplier analysis and propensity ranking-based microsimulation provide evidence of the propoor impacts of the social care expansion.
Keywords: C15; C67; D33; E24; J48; 330; social care; job creation; gender equality; pro-poor growth